2020
DOI: 10.1002/ldr.3804
|View full text |Cite
|
Sign up to set email alerts
|

Potential complementary functions among bacteria, fungi, and archaea involved in carbon cycle during reversal of desertification

Abstract: Development of biological soil crusts (BSCs) on bare land is a sign of reversal of desertification, and microbial communities of BSCs are the biogeochemical engineers of desert ecosystems. However, regulation of different microbial groups involved in the carbon (C) cycle is not clear. This study investigated the correlation between bacteria, fungi, and archaea of BSCs involved in the C cycle during reversal of desertification through community abundance analysis by quantitative PCR and functional gene detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…This exception may be due to the relatively high abundance of fungal communities in the lichen‐biocrusted soil (Figure S10); most of the functional genes are derived from bacterial rather than fungal communities (Zhao et al, 2020). Moreover, bacterial decomposers favour labile substrates (such as starch, hemicellulose and pectin), whereas fungi prefer complex substrates (such as cellulose, terpenes, chitin and vanillin/lignin; Güsewell & Gessner, 2009; Wang, Wang, et al, 2021), which is consistent with the results obtained for the lichen‐biocrusted soil.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This exception may be due to the relatively high abundance of fungal communities in the lichen‐biocrusted soil (Figure S10); most of the functional genes are derived from bacterial rather than fungal communities (Zhao et al, 2020). Moreover, bacterial decomposers favour labile substrates (such as starch, hemicellulose and pectin), whereas fungi prefer complex substrates (such as cellulose, terpenes, chitin and vanillin/lignin; Güsewell & Gessner, 2009; Wang, Wang, et al, 2021), which is consistent with the results obtained for the lichen‐biocrusted soil.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies showed that the structure and function of soil microbial communities were different under different types of biocrusts (Wang, Wang, et al, 2021; Zhao et al, 2020). Soil microorganisms can adjust their respiratory function by altering their metabolism and community structure (Brown et al, 2004), and they are the main contributors to soil respiration (Guo et al, 2020; Tian et al, 2022), especially in dryland ecosystems where vascular plants are usually quite sparse (García‐Palacios et al, 2018; Guan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While transformation genes of bacterial carbon and nitrogen were significantly associated with SOC and TN contents, transformation genes of only archaeal nitrogen were significantly associated with TN content. Wang et al ( 2021 ) reported that soil bacterial genes contributed 84.53 and 95.62% to carbon decomposition and fixation, respectively, while archaeal genes contributed only 1.09 and 4.05%, respectively, through the detection of functional genes in soils of desert ecosystem. It may be that archaea are more biased toward soil nitrogen transformation, while bacteria specialize in carbon and nitrogen transformations (Monteux et al, 2020 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al ( 2021 ) reported that soil bacterial genes contributed 84.53 and 95.62% to carbon decomposition and fixation, respectively, while archaeal genes contributed only 1.09 and 4.05%, respectively, through the detection of functional genes in soils of desert ecosystem. It may be that archaea are more biased toward soil nitrogen transformation, while bacteria specialize in carbon and nitrogen transformations (Monteux et al, 2020 ; Wang et al, 2021 ). Collectively, the abandonment of ancient rice terraces changed soil properties, such as pH and -N, which in turn altered the bacterial and archaeal community structures and reduced the gene abundance of the transformationfunctional groups of carbon and nitrogen.…”
Section: Discussionmentioning
confidence: 99%